1991
DOI: 10.1149/1.2085896
|View full text |Cite
|
Sign up to set email alerts
|

Novel Solid Redox Polymerization Electrodes: Electrochemical Properties

Abstract: The generic redox reaction of a class of linear sulfur-containing redox polymerization electrodes can be described as (--SRS--)~ + n (2e-) ~ n (-SRS-) that is, the polymer electrode can be progressively depolymerized, leading ultimately to monomeric anions, as the sulfursulfur bridges between the organic R groups are cleaved during discharge and then the monomer anions can be subsequently reoxidized back to the original polymer during charge. This is the first time the process of electrodepolymerization-electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
77
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 8 publications
0
77
0
Order By: Relevance
“…For over 15 years, organosulfur-based compounds with multiple thiol groups or disulfide moieties have received attention as potential cathode electroactive materials for lithium/lithiumion rechargeable batteries due to their high theoretical capacity and chemical tunability [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. More importantly, the capability of the thiolate system to release and capture lithium-ions during charge/discharge cycles allows their easy incorporation into the so-called "rocking-chair" type system employed in current lithium-ion battery technologies [16].…”
Section: Introductionmentioning
confidence: 99%
“…For over 15 years, organosulfur-based compounds with multiple thiol groups or disulfide moieties have received attention as potential cathode electroactive materials for lithium/lithiumion rechargeable batteries due to their high theoretical capacity and chemical tunability [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. More importantly, the capability of the thiolate system to release and capture lithium-ions during charge/discharge cycles allows their easy incorporation into the so-called "rocking-chair" type system employed in current lithium-ion battery technologies [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the redox performance of DMcT can be improved by electrocatalysts such as polyaniline (PAn) and polypyrrol (PPy). For example, Visco et al [3] and Oyama et al [4] reported that PAn can serve as an electrocatalyst to improve the redox kinetics of DMcT at room temperature. Park also reported that the charge-discharge transfer kinetics of DMcT can be enhanced by Ag and Pd nanoparticles [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] A series of compounds having -SH groups are thought to have a significant potential as energy storage materials, whereby energy exchange occurs according to a reversible polymerization-depolymerization process (2 SH ↔ S-S). 1,2 Among these compounds, 2,5-dimercapto-1,3,4-thiadiazole (DMcT) was first studied by Visco and co-workers 6 as an active cathode material for lithium secondary batteries.…”
Section: Introductionmentioning
confidence: 99%